Rapid comeback of males: evolution of male-killer suppression in a green lacewing population. Issue 1877 (25th April 2018) - Hayashi, Masayuki; Nomura, Masashi; Kageyama, Daisuke
Abstract : Evolutionary theory predicts that the spread of cytoplasmic sex ratio distorters leads to the evolution of host nuclear suppressors, although there are extremely few empirical observations of this phenomenon. Here, we demonstrate that a nuclear suppressor of a cytoplasmic male killer has spread rapidly in a population of the green lacewing Mallada desjardinsi . An M. desjardinsi population, which was strongly female-biased in 2011 because of a high prevalence of the male-killing Spiroplasma endosymbiont, had a sex ratio near parity in 2016, despite a consistent Spiroplasma prevalence. Most of the offspring derived from individuals collected in 2016 had 1 : 1 sex ratios in subsequent generations. Contrastingly, all-female or female-biased broods appeared frequently from crossings of these female offspring with males derived from a laboratory line founded by individuals collected in 2011. These results suggest near-fixation of a nuclear suppressor against male killing in 2016 and reject the notion that a non-male-killing Spiroplasma variant has spread in the population. Consistently, no significant difference was detected in mitochondrial haplotype variation between 2011 and 2016. These findings, and earlier findings in the butterfly Hypolimnas bolina in Samoa, suggest that these quick events of male recovery occur more commonly than is generally appreciated.